Coated positive electrode active material and battery using same
A coated positive electrode active material with a chlorine-based solid electrolyte layer addresses the oxidation issues in halide electrolytes, improving charging and discharging efficiency by reducing interfacial resistance and enhancing ion transfer.
Patent Information
- Application Number
- JP2022511574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2021-01-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-01-25
AI Technical Summary
Conventional batteries face challenges in improving charging and discharging efficiency due to the oxidation of halide solid electrolytes, leading to the formation of high resistance layers between the positive electrode active material and the solid electrolyte, which hinders efficient ion transfer.
A coated positive electrode active material is developed with a solid electrolyte layer that fills the recesses on the surface of the positive electrode active material, exposing convex portions, using a chlorine-based electrolyte composition to enhance oxidation resistance and reduce interfacial resistance.
The configuration reduces interfacial resistance, thereby enhancing the charging and discharging efficiency of the battery by ensuring effective ion transfer and maintaining electrolyte integrity.
Smart Images

Figure 0007611503000009 
Figure 0007611503000010 
Figure 0007611503000011
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a coated positive electrode active material and a battery using the same. [Background technology]
[0002] Patent Document 1 discloses an all-solid-state lithium battery including a positive electrode active material coated with a sulfide solid electrolyte.
[0003] Patent Document 2 discloses a positive electrode material and a secondary battery. The positive electrode material includes a positive electrode active material and a halide solid electrolyte. The halide solid electrolyte includes yttrium, chlorine, and bromine. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018 / 038037 [Patent Document 2] International Publication No. 2019 / 135322 Summary of the Invention [Problem to be solved by the invention]
[0005] In the prior art, further improvement in the charge / discharge efficiency of batteries is desired. [Means for solving the problem]
[0006] In one embodiment of the present disclosure, the coated positive electrode active material is A coated positive electrode active material comprising a particulate positive electrode active material and a solid electrolyte that coats a surface of the positive electrode active material, The solid electrolyte forms a coating layer, the coating layer is formed such that recesses on the surface of the positive electrode active material are filled with the solid electrolyte, a protrusion on the surface of the positive electrode active material is exposed on a surface of the coated positive electrode active material, The unevenness degree ζ of the particle group is defined by the following formula (1):
number
[0007] According to the present disclosure, the charge / discharge efficiency of a battery can be improved. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic configuration of a coated positive electrode active material in accordance with the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a schematic configuration of the positive electrode material in the first embodiment. [Diagram 3] FIG. 3 is a cross-sectional view showing a schematic configuration of a battery in the second embodiment. [Figure 4A] FIG. 4A is a binarized image of a cross-section obtained by observing the coated positive electrode active material of Example 1a with a scanning electron microscope. [Figure 4B]FIG. 4B is a binarized image of a cross-section obtained by observing the coated positive electrode active material of Comparative Example 1a with a scanning electron microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.
[0010] The following descriptions are all comprehensive or specific examples. The numerical values, compositions, shapes, film thicknesses, electrical characteristics, secondary battery structures, electrode materials, etc. shown below are merely examples and are not intended to limit the present disclosure. In addition, components not described in the independent claims showing the highest concept are optional components.
[0011] (Findings on which this disclosure is based) In Patent Document 1, the positive electrode active material is coated with a sulfide solid electrolyte. The sulfide solid electrolyte is a material with high ionic conductivity, but has a problem with oxidation resistance.
[0012] A halide solid electrolyte containing bromine is used in Patent Document 2. As a result of intensive research, the present inventors have found that when a halide solid electrolyte containing bromine is contained in a positive electrode material, the halide solid electrolyte is oxidized and decomposed during charging of the battery, and the charge / discharge efficiency of the battery is accordingly reduced.
[0013] Specifically, in a material containing bromine as an anion constituting a solid electrolyte, when a positive electrode active material with an average potential against Li of 3.7 V or more is used, the solid electrolyte may decompose due to an oxidation reaction during charging, and the oxidative decomposition product may function as a resistance layer. Here, the oxidation reaction means a side reaction in which electrons are extracted from the solid electrolyte containing an anion in contact with the positive electrode active material, in addition to the normal charging reaction in which lithium and electrons are extracted from the positive electrode active material in the positive electrode material. As a result of this oxidation reaction, an oxidative decomposition layer with poor lithium ion conductivity is formed between the positive electrode active material and the solid electrolyte, and it is believed that the oxidative decomposition layer functions as a large interface resistance.
[0014] Bromine has a smaller electronegativity and a larger ionic radius than chlorine. Therefore, it is considered that the interaction between the cationic components constituting the halide solid electrolyte and bromine is weak, and bromine is easily oxidized. Therefore, it is considered that a battery using a solid electrolyte in which the anion constituting the solid electrolyte is chlorine exhibits excellent oxidation resistance and can improve the charge / discharge efficiency of the battery.
[0015] In order to suppress the oxidative decomposition of the solid electrolyte and suppress the formation of a high resistance layer between the positive electrode active material and the solid electrolyte, it is necessary to select a solid electrolyte with excellent oxidation resistance. In addition, in order to improve the charge / discharge efficiency of the battery, it is necessary to reduce the interface resistance between the positive electrode active material and the solid electrolyte. However, in a battery using a positive electrode active material coated with a solid electrolyte, it has been difficult to simultaneously suppress the formation of a high resistance layer and improve the charge / discharge efficiency of the battery.
[0016] Based on the above findings, the present inventors have come up with the idea of forming a coating layer using a solid electrolyte in which the anion constituting the solid electrolyte is chlorine, and have found that this can suppress the oxidation reaction of the solid electrolyte and further improve the charge / discharge efficiency of the battery.
[0017] As a result of further intensive research, the present inventors have found that a structure in which the concave portions of the unevenness on the surface of the positive electrode active material are filled with a solid electrolyte and the convex portions of the unevenness on the surface of the positive electrode active material are exposed on the surface of the coated positive electrode active material is effective for reducing the interfacial resistance. In other words, the present inventors have found that by realizing a coated positive electrode active material having a smooth surface, the interfacial resistance between the positive electrode active material and the solid electrolyte can be reduced and the charge / discharge efficiency of the battery can be further improved.
[0018] (Summary of one aspect of the present disclosure) A coated positive electrode active material comprising a particulate positive electrode active material and a solid electrolyte that coats a surface of the positive electrode active material, The solid electrolyte forms a coating layer, the coating layer is formed such that recesses on the surface of the positive electrode active material are filled with the solid electrolyte, a protrusion on the surface of the positive electrode active material is exposed on a surface of the coated positive electrode active material, The unevenness degree ζ of the particle group is defined by the following formula (1):
number
[0019] According to the first aspect, the charge / discharge efficiency of the battery can be improved.
[0020] In the second aspect of the present disclosure, for example, in the coated cathode active material according to the first aspect, the ratio of the mass of the solid electrolyte to the mass of the cathode active material may be in the range of 3 / 100 or more and 1 / 10 or less. According to the second aspect, the interface resistance between the cathode active material and the solid electrolyte can be reduced. This can improve the charge / discharge efficiency of the battery.
[0021] In a third aspect of the present disclosure, for example, in the coated cathode active material according to the first aspect, the ratio of the mass of the solid electrolyte to the mass of the cathode active material may be in the range of 1 / 20 or more and 7 / 100 or less. According to the third aspect, the charge / discharge efficiency of the battery can be further improved.
[0022] In a fourth aspect of the present disclosure, for example, in the coated cathode active material according to any one of the first to third aspects, when the total perimeter of the outline of the cathode active material in a cross-sectional image of the coated cathode active material is defined as L and the total length of the contact portion between the cathode active material and the coating layer is defined as C, the coverage ratio represented by the ratio C / L of the total length C to the total perimeter L may be in the range of 0.3 to 0.95. According to the fourth aspect, the interface resistance between the cathode active material and the solid electrolyte can be reduced. This can improve the charge / discharge efficiency of the battery.
[0023] In the fifth aspect of the present disclosure, for example, in the coated cathode active material according to any one of the first to fourth aspects, the average thickness of the coating layer may be in the range of 1 nm or more and 300 nm or less. According to the fifth aspect, the interface resistance between the cathode active material and the solid electrolyte can be reduced. This can improve the charge / discharge efficiency of the battery.
[0024] In the sixth aspect of the present disclosure, for example, in the coated positive electrode active material according to any one of the first to fourth aspects, the average thickness of the coating layer may be in the range of 2 nm or more and 200 nm or less. According to the sixth aspect, the interface resistance between the positive electrode active material and the solid electrolyte can be reduced. This can improve the charge / discharge efficiency of the battery.
[0025] In a seventh aspect of the present disclosure, for example, in the coated cathode active material according to any one of the first to sixth aspects, M may contain yttrium. According to the seventh aspect, the ionic conductivity of the solid electrolyte can be further improved. This can further improve the charge / discharge efficiency of the battery.
[0026] In the eighth aspect of the present disclosure, for example, in the coated cathode active material according to any one of the first to seventh aspects, α, β, and γ may satisfy 2.5≦α≦3, 1≦β≦1.1, and γ=6, respectively. According to the eighth aspect, the ionic conductivity of the solid electrolyte can be further improved. This can further improve the charge / discharge efficiency of the battery.
[0027] In a ninth aspect of the present disclosure, for example, in the coated positive electrode active material according to any one of the first to eighth aspects, the positive electrode active material may contain lithium nickel-cobalt-manganese oxide. According to the ninth aspect, the energy density of the battery can be further increased.
[0028] In a tenth aspect of the present disclosure, for example, in the coated cathode active material according to any one of the first to ninth aspects, the cathode active material may have a surface layer containing lithium metal oxide. According to the tenth aspect, the charge / discharge efficiency of the battery can be further improved.
[0029] In an eleventh aspect of the present disclosure, for example, in the coated positive electrode active material according to the tenth aspect, the lithium metal oxide may contain lithium niobate. According to the eleventh aspect, the charge / discharge efficiency of the battery can be further improved.
[0030] The positive electrode material according to the twelfth aspect of the present disclosure comprises: A coated positive electrode active material according to any one of the first to eleventh aspects; A positive electrode solid electrolyte; Includes.
[0031] By using the coated positive electrode active material of the present disclosure as a positive electrode material, a battery having excellent charge / discharge efficiency can be obtained.
[0032] In a thirteenth aspect of the present disclosure, for example, in the positive electrode material according to the twelfth aspect, the positive electrode solid electrolyte may include a halide solid electrolyte. The halide solid electrolyte exhibits excellent ion conductivity.
[0033] In a fourteenth aspect of the present disclosure, for example, in the positive electrode material according to the twelfth or thirteenth aspect, the positive electrode solid electrolyte may include a sulfide solid electrolyte. The sulfide solid electrolyte exhibits excellent ion conductivity.
[0034] A battery according to a fifteenth aspect of the present disclosure comprises: A positive electrode comprising a positive electrode material according to any one of the twelfth to fourteenth aspects; A negative electrode; an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with.
[0035] According to the fifteenth aspect, by using the positive electrode material of the present disclosure in the positive electrode, a battery having excellent charge / discharge efficiency can be obtained.
[0036] In a sixteenth aspect of the present disclosure, for example, in the battery according to the fifteenth aspect, the electrolyte layer may contain at least one selected from the group consisting of a solid electrolyte having the same composition as the solid electrolyte contained in the coating layer and a solid electrolyte having the same composition as the positive electrode solid electrolyte. According to the sixteenth aspect, the charge and discharge characteristics of the battery can be further improved.
[0037] In a seventeenth aspect of the present disclosure, for example, in the battery according to the fifteenth aspect, the electrolyte layer may contain a halide solid electrolyte having a composition different from that of the solid electrolyte contained in the coating layer and / or the positive electrode solid electrolyte. According to the seventeenth aspect, the charge and discharge characteristics of the battery can be further improved.
[0038] In an eighteenth aspect of the present disclosure, for example, in the battery according to any one of the fifteenth to seventeenth aspects, the electrolyte layer may contain a sulfide solid electrolyte. According to the eighteenth aspect, the charge and discharge characteristics of the battery can be further improved.
[0039] A manufacturing method according to a nineteenth aspect of the present disclosure includes the steps of: A method for producing a coated positive electrode active material according to any one of the first to eleventh aspects, The positive electrode active material and the solid electrolyte are treated by a dry particle composite method, The treatment by the dry particle composite method includes imparting at least one mechanical energy selected from the group consisting of impact, compression, and shear to the positive electrode active material and the solid electrolyte.
[0040] According to the nineteenth aspect, a desired coated positive electrode active material can be produced.
[0041] In a twentieth aspect of the present disclosure, for example, in the production method according to the nineteenth aspect, a ratio Da / Dc of an average particle diameter Da of the positive electrode active material to an average particle diameter Dc of the solid electrolyte may be equal to or greater than 2. According to the twentieth aspect, the interfacial resistance between the positive electrode active material and the coating layer is reduced, and the charge / discharge efficiency of the battery can be further improved.
[0042] In a 21st aspect of the present disclosure, for example, in the production method according to the 19th aspect, the ratio Da / Dc of the average particle diameter Da of the positive electrode active material to the average particle diameter Dc of the solid electrolyte may be equal to or greater than 5. According to the 21st aspect, the interfacial resistance between the positive electrode active material and the coating layer is further reduced, and the charge / discharge efficiency of the battery can be further improved.
[0043] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0044] (Embodiment 1) (Coated positive electrode active material) FIG. 1 is a cross-sectional view showing a schematic configuration of a coated positive electrode active material 100 in the first embodiment.
[0045] The coated cathode active material 100 in the first embodiment includes a particulate cathode active material 101 and a solid electrolyte 102 that coats the surface of the cathode active material 101. The solid electrolyte 102 forms a coating layer. The coating layer is formed such that recesses on the surface of the cathode active material 101 are filled with the solid electrolyte 102. Protrusions on the surface of the cathode active material 101 are exposed on the surface of the coated cathode active material 100.
[0046] Here, the unevenness ζ of the particle group is defined by the following formula (1).
[0047]
number
[0048] In formula (1), n is an integer of 3 or more representing the number of particles measured. The upper limit of n is not particularly limited, and is, for example, 50. Lpi represents the total perimeter of the outline of the cross-sectional image of each particle. Lei represents the total perimeter of an equivalent smooth ellipse having a major-minor ratio and area equal to the major-minor ratio and area of the cross-sectional image of each particle. The major-minor ratio represents the ratio of the minor axis of the cross-sectional image to the major axis of the cross-sectional image. Lpi and Lei can be calculated from a binary image of a cross-sectional SEM image obtained by observing the cross-section of a particle with a scanning electron microscope (SEM).
[0049] The degree of unevenness ζ represents the degree of unevenness of the outline of the positive electrode active material 101 and the degree of unevenness of the outline of the coated positive electrode active material 100. The degree of unevenness ζ satisfies 0≦ζ≦1. The closer the particle shape is to a smooth ellipse (circle), the closer the degree of unevenness ζ is to 1. The greater the degree of unevenness of the particle, the closer the degree of unevenness ζ is to 0.
[0050] In this specification, the unevenness of the particle group of the positive electrode active material 101 is defined as ζ1. The unevenness of the particle group of the coated positive electrode active material 100 is defined as ζ2. The unevenness ζ1 of the positive electrode active material 101 can be calculated from the perimeter Lp of the particle of the positive electrode active material 101 excluding the coating layer and the perimeter Le of the equivalent smooth ellipse in the binary image of the cross-sectional SEM image of the particle of the coated positive electrode active material 100. The equivalent smooth ellipse is an ellipse having a long-short ratio and an area equal to the long-short ratio and cross-sectional area of the particle of the positive electrode active material 101. The unevenness ζ2 of the coated positive electrode active material 100 can be calculated from the perimeter Lp' of the particle of the coated positive electrode active material 100 including the coating layer and the perimeter Le' of the equivalent smooth ellipse in the binary image of the cross-sectional SEM image of the particle of the coated positive electrode active material 100. The equivalent smooth ellipse is an ellipse having a long-short ratio and an area equal to the long-short ratio and cross-sectional area of a particle of coated positive electrode active material 100 .
[0051] In addition, when the coating layer is not in contact with the surface of the positive electrode active material 101 and is floating (peeled off) from the positive electrode active material 101, the floating portion is excluded from the coating layer to calculate each overall perimeter length. In other words, the floating portion is not considered to be the coating layer and is not treated as the coating layer. The same applies to the case of specifying the equivalent smooth ellipse. This interpretation is also applied to the calculation of the coverage rate described later.
[0052] In coated positive electrode active material 100 of the present embodiment, the degree of unevenness change R defined by the following formula (2) is 1.1 or more.
[0053] R = ζ2 / ζ1 (2)
[0054] That is, the unevenness change degree R in the coated positive electrode active material 100 is defined as the ratio (ζ2 / ζ1) of the unevenness degree ζ2 of the coated positive electrode active material 100 to the unevenness degree ζ1 of the positive electrode active material 101. The upper limit of the unevenness change degree R is the value when the contour of the coated positive electrode active material 100 is a perfect circle. That is, when the unevenness degree ζ2 of the coated positive electrode active material 100 is 1, the unevenness change degree R takes its upper limit. The upper limit of the unevenness change degree R is 1 / ζ1. For example, if the lower limit of the unevenness degree (average value) of the positive electrode active material 101 is 0.5, the upper limit of the unevenness change degree R is 2.0.
[0055] By covering the recesses of the unevenness of the surface of the positive electrode active material 101 so as to be filled with the solid electrolyte 102 and realizing a smooth coated positive electrode active material 100, the interface resistance between the positive electrode active material 101 and the solid electrolyte 102 can be reduced. It can be said that the unevenness change degree R simply expresses the degree to which the recesses are filled with the solid electrolyte 102. In addition, by exposing at least one protrusion of the unevenness of the surface of the positive electrode active material 101 to the surface (outermost surface) of the coated positive electrode active material 100, the electronic conductivity between adjacent coated positive electrode active materials 100 can be ensured. In other words, the electronic conductivity between the particles of the coated positive electrode active material 100 is sufficiently ensured by the contact between the protrusions. From this viewpoint, it is desirable that a plurality of protrusions are exposed to the surface (outermost surface) of the coated positive electrode active material 100. In that case, the probability of contact between the protrusions is increased. It is not essential that the entire protrusions are exposed. The above-mentioned effect can be obtained even if only a part of the protrusions is exposed.
[0056] According to the above configuration, the charge / discharge efficiency of the battery can be improved.
[0057] In the coated positive electrode active material 100, the ratio of the mass of the solid electrolyte 102 to the mass of the positive electrode active material 101 may be in the range of 3 / 100 or more and 1 / 10 or less. If the ratio of the mass of the solid electrolyte 102 is 3 / 100 or more, the proportion of the solid electrolyte 102 covering the surface of the positive electrode active material 101 is sufficiently high, so that the recesses can be sufficiently filled with the solid electrolyte 102. If the ratio of the mass of the solid electrolyte 102 is 1 / 10 or less, the solid electrolyte 102 covering the surface of the positive electrode active material 101 is unlikely to hinder electron transfer between the positive electrode active materials 101. In this case, a battery using the coated positive electrode active material 100 as a positive electrode material can achieve excellent charge and discharge efficiency.
[0058] The above-described configuration can reduce the interface resistance between the positive electrode active material 101 and the solid electrolyte 102. This can improve the charge / discharge efficiency of the battery.
[0059] In the coated positive electrode active material 100, the ratio of the mass of the solid electrolyte 102 to the mass of the positive electrode active material 101 may be in the range of 1 / 20 or more and 7 / 100 or less.
[0060] According to the above configuration, the charge / discharge efficiency of the battery can be further improved.
[0061] In the cross-sectional image of the coated positive electrode active material 100, the total perimeter of the outline of the positive electrode active material 101 is defined as L, and the total length of the contact portion between the positive electrode active material 101 and the coating layer is defined as C. In this case, the coverage expressed by the ratio C / L of the total length C to the total perimeter L may be in the range of 0.3 or more and 0.95 or less. When the coverage is 0.3 or more, the recesses are sufficiently filled with the solid electrolyte 102. When the coverage is 0.95 or less, the solid electrolyte 102 that covers the surface of the positive electrode active material 101 is unlikely to hinder the electron transfer between the positive electrode active materials 101. In this case, a battery using the coated positive electrode active material 100 as a positive electrode material can achieve excellent charge / discharge efficiency.
[0062] The above-described configuration can reduce the interface resistance between the positive electrode active material 101 and the solid electrolyte 102. This can improve the charge / discharge efficiency of the battery.
[0063] The coverage may be in the range of 0.7 to 0.92.
[0064] According to the above configuration, the charge / discharge efficiency of the battery can be further improved.
[0065] The coverage can be calculated from a binarized image of the cross-sectional SEM image of the coated positive electrode active material 100. In the same field of view of the cross-sectional SEM image of the coated positive electrode active material 100, the total perimeter length L of the outline of the positive electrode active material 101 and the total length C of the contact portion between the positive electrode active material 101 and the coating layer can be obtained by image processing. The ratio C / L is defined as the coverage of the coating layer of the coated positive electrode active material 100. Note that when the coating layer is not in contact with the surface of the positive electrode active material 101 and the coating layer is floating above the positive electrode active material 101, the part is excluded from the contact portion to calculate the total length C. In other words, the part is not considered as the contact portion.
[0066] The average thickness of the coating layer may be, for example, in the range of 1 nm or more and 300 nm or less. When the average thickness of the coating layer is 1 nm or more, the recesses can be sufficiently filled with the solid electrolyte 102. When the average thickness of the coating layer is 300 nm or less, the solid electrolyte 102 that covers the surface of the positive electrode active material 101 is less likely to hinder electron transfer between the positive electrode active materials 101. The average thickness of the coating layer can be obtained, for example, by measuring the thickness of the coating layer at any 16 points from a cross-sectional SEM image of the coated positive electrode active material 100 obtained by a scanning electron microscope, and calculating an average value from the measured values. The average thickness of the coating layer may be in the range of 2 nm or more and 200 nm or less.
[0067] The above-described configuration can reduce the interface resistance between the positive electrode active material 101 and the solid electrolyte 102. This can improve the charge / discharge efficiency of the battery.
[0068] (Solid electrolyte 102 constituting the coating layer) As the solid electrolyte 102 constituting the coating layer, a material having lithium ion conductivity, low electronic conductivity, and oxidation resistance can be used.
[0069] An ionic crystalline halide solid electrolyte material may be used as the solid electrolyte 102. The halide solid electrolyte material may be free of sulfur.
[0070] A material may be used in which the anions constituting the solid electrolyte 102 are chlorine ions. In other words, a material in which the anions constituting the solid electrolyte 102 are only chloride ions may be used.
[0071] More specifically, the solid electrolyte 102 has a composition represented by the following formula (3): In formula (3), α, β, and γ are greater than 0, and M includes at least one element selected from the group consisting of metal elements and semi-metal elements other than Li.
[0072] Li α M β Cl γ (3)
[0073] "Metalloid elements" includes B, Si, Ge, As, Sb, and Te.
[0074] "Metal elements" include all elements in groups 1 to 12 of the periodic table except hydrogen, and all elements in groups 13 to 16 except B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se. In other words, "metal elements" are a group of elements that can become cations when forming inorganic compounds with halogen compounds.
[0075] When solid electrolyte 102 contains at least one element selected from the group consisting of metal elements and metalloid elements other than Li, the solid electrolyte 102 has a higher ionic conductivity than solid electrolyte 102 such as LiI that is composed only of Li and halogen elements. Therefore, when solid electrolyte 102 containing at least one element selected from the group consisting of metal elements and metalloid elements other than Li is used in a battery, the charge / discharge efficiency of the battery can be improved.
[0076] In the formula (3), M may contain yttrium. That is, the solid electrolyte 102 may contain Y as a metal element.
[0077] According to the above configuration, the ionic conductivity of the solid electrolyte 102 can be further improved. Thereby, the charge and discharge efficiency of the battery can be further improved.
[0078] The solid electrolyte 102 containing Y may be a compound represented by the composition formula of Li a Me b Y c Cl6, where a + mb + 3c = 6 and c > 0 are satisfied. Me is at least one selected from the group consisting of metal elements and metalloid elements excluding Li and Y. m is the valence of Me.
[0079] As Me, at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, Gd, Sm, Tb, and Nb may be used.
[0080] According to the above configuration, the ionic conductivity of the solid electrolyte 102 can be further improved.
[0081] In formula (3), 2.5 ≤ α ≤ 3, 1 ≤ β ≤ 1.1, and γ = 6 may be satisfied.
[0082] According to the above configuration, the ionic conductivity of the solid electrolyte 102 can be further improved. Thereby, the charge and discharge efficiency of the battery can be further improved.
[0083] The solid electrolyte 102 may have a composition represented by the following formula (A1). In formula (A1), 0 < d < 2 is satisfied.
[0084] Li 6-3d Y d Cl6···(A1)
[0085] According to the above configuration, the ionic conductivity of the solid electrolyte 102 can be further improved. Thereby, the charge and discharge efficiency of the battery can be further improved.
[0086] The solid electrolyte 102 may have a composition represented by the following formula (A2):
[0087] Li3YCl6···(A2)
[0088] The above configuration can further improve the ionic conductivity of the solid electrolyte 102. This can further improve the charge / discharge efficiency of the battery.
[0089] The solid electrolyte 102 may have a composition represented by the following formula (A3): In formula (A3), 0<δ≦0.15 is satisfied.
[0090] Li 3-3δ Y 1+δ Cl6···(A3)
[0091] The above configuration can further improve the ionic conductivity of the solid electrolyte 102. This can further improve the charge / discharge efficiency of the battery.
[0092] The "solid electrolyte" in the present disclosure is not limited to one that strictly satisfies the above composition formula, but also includes one that contains a trace amount of impurities other than the constituent elements represented by the composition formula. For example, in the coating material, the impurities contained in the constituent elements other than the constituent elements represented by the composition formula may be 10 mol % or less.
[0093] (Method of Manufacturing Solid Electrolyte 102) The solid electrolyte 102 (first solid electrolyte) in the first embodiment can be produced by the following method.
[0094] Prepare raw material powders of halides that will produce the desired composition. For example, to produce Li3YCl6, prepare LiCl and YCl3 in a molar ratio of 3:1. By selecting the type of raw material powder, you can determine the "M" and "Me" in the above composition formula. You can also adjust the above values of "α", "β", "γ", "d" and "δ" by adjusting the raw materials, the composition ratio and the synthesis process.
[0095] After the raw material powders are thoroughly mixed, the raw material powders are mixed, pulverized, and reacted with each other using a mechanochemical milling method. Alternatively, after the raw material powders are thoroughly mixed, the mixed powder may be fired in a vacuum or in an inert atmosphere. The firing conditions may be, for example, within a range of 100° C. or higher and 650° C. or lower, for 1 hour or more. As a result, a solid electrolyte 102 having the composition described above is obtained.
[0096] The constitution of the crystal phase (crystal structure) in the coating material can be determined by adjusting the reaction method and reaction conditions of the raw material powders.
[0097] (Cathode active material 101) The positive electrode active material 101 is, for example, a material having a property of absorbing and releasing metal ions (for example, lithium ions). Examples of the positive electrode active material 101 include lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, and transition metal oxynitrides. Examples of the lithium-containing transition metal oxides include Li(Ni,Co,Al)O2, Li(Ni,Co,Mn)O2, and LiCoO2. One or a mixture of two or more selected from these can be used as the positive electrode active material 101.
[0098] When a lithium-containing transition metal oxide is used as the positive electrode active material 101, the manufacturing cost of the positive electrode can be reduced and the average discharge voltage can be increased.
[0099] The positive electrode active material 101 may contain lithium nickel-cobalt-manganese oxide. The positive electrode active material 101 may contain Li(NiCoMn)O2. As the positive electrode active material 101, only lithium nickel-cobalt-manganese oxide may be used. With the above configuration, the energy density of the battery can be further increased.
[0100] There is no particular limitation on the shape of the particles of the positive electrode active material 101. The shape of the particles of the positive electrode active material 101 may be spherical, oval spherical, scaly, or fibrous.
[0101] In the first embodiment, the positive electrode active material 101 may have a surface layer containing lithium metal oxide. The lithium metal oxide constituting the surface layer has a composition different from that of the lithium-containing transition metal oxide constituting the main body (excluding the surface layer) of the positive electrode active material 101. LiNbO3 (lithium niobate) or the like can be used as the lithium metal oxide. When the positive electrode active material 101 has a surface layer containing LiNbO3, a side reaction between the positive electrode active material 101 and the coating layer during charging is suppressed. Therefore, according to this configuration, the coated positive electrode active material 100 in the first embodiment can effectively suppress the generation of a high resistance layer on the surface of the positive electrode active material 101. As a result, the charge / discharge efficiency of the battery can be further improved.
[0102] When the positive electrode active material 101 has the above-mentioned surface layer, the surface layer is also considered to be a part of the positive electrode active material 101 .
[0103] (Method of manufacturing the coated positive electrode active material 100) The method for producing the coated cathode active material 100 in the first embodiment includes, for example, treating the cathode active material 101 and the solid electrolyte 102 constituting the coating layer by a dry particle compositing method. The treatment by the dry particle compositing method includes applying at least one mechanical energy selected from the group consisting of impact, compression, and shear to the cathode active material 101 and the solid electrolyte 102. The cathode active material 101 and the solid electrolyte 102 are mixed in an appropriate ratio.
[0104] According to the above method, the desired coated positive electrode active material 100 can be produced.
[0105] The apparatus that can be used in the manufacturing method of the coated positive electrode active material 100 is not particularly limited, and can be an apparatus that can impart mechanical energy such as impact, compression, and shear to the mixture. Examples of the apparatus that can impart mechanical energy include a ball mill, and a compression shear processing apparatus (particle composite apparatus) such as "Mechanofusion" (manufactured by Hosokawa Micron Corporation) and "Nobilta" (manufactured by Hosokawa Micron Corporation). Among these, "Mechanofusion" and "Nobilta" are preferable, and "Nobilta" is more preferable.
[0106] "Mechanofusion" is a particle compounding device that uses dry mechanical compounding technology by applying strong mechanical energy to multiple different material particles. In Mechanofusion, the powder raw materials are fed between a rotating container and a press head, and mechanical energy such as compression, shear, and friction is applied to them, causing the particles to compound.
[0107] "Nobilta" is a particle compositing device that uses dry mechanical compositing technology, an advanced particle compositing technology, to composite nanoparticles as raw materials. Nobilta produces composite particles by applying mechanical energy of impact, compression, and shear to multiple raw material powders.
[0108] In the "Nobilta", a rotor arranged to have a specified gap between itself and the inner wall of a horizontal cylindrical mixing vessel rotates at high speed, and the raw material powder is forced to pass through the gap, and this process is repeated multiple times. This applies impact, compression, and shear forces to the mixture, making it possible to produce composite particles of positive electrode active material 101 and solid electrolyte 102. Conditions such as the rotor rotation speed, processing time, and feed amount can be adjusted as appropriate.
[0109] In manufacturing the coated cathode active material 100, a powder of the solid electrolyte 102 is used. The ratio Da / Dc of the average particle diameter Da of the cathode active material 101 to the average particle diameter Dc of the solid electrolyte 102 may be 2 or more. In this case, the recesses of the uneven portion on the surface of the cathode active material 101 are densely filled with the solid electrolyte 102. As a result, the interface resistance between the cathode active material 101 and the coating layer is reduced, and the charge / discharge efficiency of the battery can be further improved.
[0110] The ratio Da / Dc may be equal to or greater than 5. In this case, the recesses of the uneven surface of the positive electrode active material 101 are more densely filled with the solid electrolyte 102. As a result, the interface resistance between the positive electrode active material 101 and the coating layer is further reduced, and the charge / discharge efficiency of the battery can be further improved.
[0111] The average particle size of the positive electrode active material 101 and the coating material can be measured, for example, using SEM images. Specifically, the average particle size of the positive electrode active material 101 and the solid electrolyte 102 is obtained by calculating the average circle-equivalent diameter of 50 arbitrarily selected particles of the positive electrode active material 101 and 50 arbitrarily selected particles of the solid electrolyte 102 using the SEM images. The "circle-equivalent diameter" means the diameter of a circle having an area equal to the area of the image of a specific particle.
[0112] (Positive electrode material 1000) FIG. 2 is a cross-sectional view showing a schematic configuration of the positive electrode material 1000 in the first embodiment.
[0113] The positive electrode material 1000 in the first embodiment includes the coated positive electrode active material 100 in the first embodiment described above and a positive electrode solid electrolyte 202. By using the coated positive electrode active material 100 in the first embodiment as a positive electrode material, a battery having excellent charge / discharge efficiency can be obtained.
[0114] The positive electrode solid electrolyte 202 includes, for example, a solid electrolyte having high ionic conductivity.
[0115] The positive electrode solid electrolyte 202 may have the same composition as the solid electrolyte 102 constituting the coating layer. As the positive electrode solid electrolyte 202, for example, Li3YCl6 or the like can be used.
[0116] The positive electrode solid electrolyte 202 may include a halide solid electrolyte. Examples of the halide solid electrolyte include Li3(Ca,Y,Gd)X6, Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, and LiI. In these solid electrolytes, the element X is at least one selected from the group consisting of Cl, Br, and I. In this disclosure, when an element in a formula is expressed as "(Al,Ga,In)", this notation indicates at least one element selected from the group of elements in parentheses. That is, "(Al,Ga,In)" is synonymous with "at least one selected from the group consisting of Al, Ga, and In". The same applies to other elements. The halide solid electrolyte exhibits excellent ion conductivity.
[0117] The positive electrode solid electrolyte 202 may be a halide solid electrolyte. For example, the halide solid electrolyte includes lithium, yttrium, chlorine and bromine. The halide solid electrolyte may be Li3YBr2Cl4.
[0118] The positive electrode solid electrolyte 202 may include a sulfide solid electrolyte. Examples of the sulfide solid electrolyte include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, and Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 These can be used in combination with LiX, Li2O, MO q , Li p MO q In this case, the element X in "LiX" is one or more elements selected from the group consisting of F, Cl, Br, and I. q " and "Li p MOq "The element M is one or more elements selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe, and Zn. q " and "Li p MO q " In this equation, p and q are independent natural numbers.
[0119] The positive electrode solid electrolyte 202 may be a sulfide solid electrolyte. For example, the sulfide solid electrolyte may include lithium sulfide and phosphorus sulfide. For example, the sulfide solid electrolyte may be Li2S-P2S5. The sulfide solid electrolyte exhibits excellent ionic conductivity.
[0120] As the positive electrode solid electrolyte 202, one type or a mixture of two or more types selected from the solid electrolytes described above can be used.
[0121] The shape of the positive electrode solid electrolyte 202 is not particularly limited. The shape of the positive electrode solid electrolyte 202 may be needle-like, spherical, elliptical, etc. The shape of the positive electrode solid electrolyte 202 may be particles.
[0122] When the shape of the positive electrode solid electrolyte 202 is particulate (e.g., spherical), the median diameter of the positive electrode solid electrolyte 202 may be 100 μm or less. When the median diameter of the positive electrode solid electrolyte 202 is 100 μm or less, the coated positive electrode active material 100 and the positive electrode solid electrolyte 202 can form a good dispersion state in the positive electrode material 1000. As a result, the charge and discharge characteristics of a battery using the positive electrode material 1000 are improved.
[0123] The median diameter of the positive electrode solid electrolyte 202 may be 10 μm or less. With this configuration, in the positive electrode material 1000, the coated positive electrode active material 100 and the positive electrode solid electrolyte 202 can form a better dispersed state.
[0124] The median diameter of the positive electrode solid electrolyte 202 may be smaller than the median diameter of the coated positive electrode active material 100. According to this configuration, in the positive electrode material 1000, the coated positive electrode active material 100 and the positive electrode solid electrolyte 202 can form a better dispersed state.
[0125] The median diameter of the coated positive electrode active material 100 may be 0.1 μm or more and 100 μm or less.
[0126] When the median diameter of the coated positive electrode active material 100 is 0.1 μm or more, the coated positive electrode active material 100 and the positive electrode solid electrolyte 202 can form a good dispersion state in the positive electrode material 1000. As a result, the charge / discharge characteristics of a battery using the positive electrode material 1000 are improved. In addition, when the median diameter of the coated positive electrode active material 100 is 100 μm or less, the lithium diffusion rate in the coated positive electrode active material 100 is improved. As a result, a battery using the positive electrode material 1000 can operate at high output.
[0127] The median diameter of coated positive electrode active material 100 may be larger than the median diameter of positive electrode solid electrolyte 202. This allows coated positive electrode active material 100 and positive electrode solid electrolyte 202 to form a good dispersed state.
[0128] In the positive electrode material 1000, the positive electrode solid electrolyte 202 and the coating layer of the coated positive electrode active material 100 may be in contact with each other.
[0129] Moreover, the positive electrode material 1000 in the first embodiment may include a plurality of positive electrode solid electrolytes 202 and a plurality of coated positive electrode active materials 100 .
[0130] In addition, in the positive electrode material 1000 in the first embodiment, the content of the positive electrode solid electrolyte 202 and the content of the coated positive electrode active material 100 may be the same as or different from each other.
[0131] (Embodiment 2) Hereinafter, the second embodiment will be described. Descriptions that overlap with the first embodiment will be omitted as appropriate.
[0132] FIG. 3 is a cross-sectional view showing a schematic configuration of a battery in the second embodiment.
[0133] The battery 300 in the second embodiment includes a positive electrode 301 including the positive electrode material 1000 described in the first embodiment above, an electrolyte layer 302, and a negative electrode 303. By using the positive electrode material 1000 in the positive electrode 301, the battery 300 has excellent charge / discharge efficiency.
[0134] The positive electrode 301 includes a material having the property of absorbing and releasing metal ions (for example, lithium ions). The positive electrode 301 includes a coated positive electrode active material 100 and a positive electrode solid electrolyte 202.
[0135] When the volume ratio of the positive electrode active material 101 to the total of the solid electrolyte 102 and the positive electrode solid electrolyte 202 contained in the positive electrode 301 is "v1:100-v1", 30≦v1≦95 may be satisfied. Here, v1 indicates the volume fraction of the positive electrode active material 101 when the total volume of the positive electrode active material 101, the solid electrolyte 102, and the positive electrode solid electrolyte 202 contained in the positive electrode 301 is taken as 100. When 30≦v1 is satisfied, it is easy to ensure a sufficient energy density of the battery 300. When v1≦95 is satisfied, it becomes easier for the battery 300 to operate at high output.
[0136] The thickness of the positive electrode 301 may be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 301 is 10 μm or more, a sufficient energy density of the battery 300 can be ensured. When the thickness of the positive electrode 301 is 500 μm or less, high-output operation of the battery 300 can be achieved.
[0137] The electrolyte layer 302 is disposed between the positive electrode 301 and the negative electrode 303 .
[0138] The electrolyte layer 302 is a layer including an electrolyte material. The electrolyte material may include, for example, a solid electrolyte (second solid electrolyte). That is, the electrolyte layer 302 may be a solid electrolyte layer.
[0139] The solid electrolyte contained in the electrolyte layer 302 may be at least one selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.
[0140] Electrolyte layer 302 may contain at least one selected from the group consisting of a solid electrolyte having the same composition as solid electrolyte 102 contained in the coating layer of coated cathode active material 100 and a solid electrolyte having the same composition as cathode solid electrolyte 202 .
[0141] When the electrolyte layer 302 includes a halide solid electrolyte, the halide solid electrolyte may have the same composition as the halide solid electrolyte included in the solid electrolyte 102, or may have the same composition as the halide solid electrolyte included in the positive electrode solid electrolyte 202. When the composition of the halide solid electrolyte included in the solid electrolyte 102 is different from the composition of the halide solid electrolyte included in the positive electrode solid electrolyte 202, the electrolyte layer 302 may include those halide solid electrolytes having different compositions from each other.
[0142] According to the above configuration, the charge / discharge characteristics of the battery 300 can be further improved.
[0143] The electrolyte layer 302 may include a halide solid electrolyte having a composition different from the composition of the solid electrolyte 102 included in the coating layer and / or the composition of the positive electrode solid electrolyte 202 .
[0144] According to the above configuration, the charge / discharge characteristics of the battery 300 can be further improved.
[0145] The electrolyte layer 302 may include a sulfide solid electrolyte. The sulfide solid electrolyte included in the electrolyte layer 302 may have the same composition as the sulfide solid electrolyte included in the positive electrode solid electrolyte 202.
[0146] According to the above configuration, the charge / discharge characteristics of the battery can be further improved.
[0147] When the electrolyte layer 302 contains a sulfide solid electrolyte having excellent reduction stability, a low potential negative electrode material such as graphite or metallic lithium can be used for the negative electrode 303. This allows the energy density of the battery 300 to be improved.
[0148] The electrolyte layer 302 may contain an oxide solid electrolyte. Examples of the oxide solid electrolyte contained in the electrolyte layer 302 include NASICON-type solid electrolyte materials such as LiTi2(PO4)3 and its elemental substitutes, (LaLi)TiO3-based perovskite-type solid electrolyte materials, Li 14 ZnGeO 16 , Li4SiO4, LiGeO4 and their elemental substitutions as representative LISICON-type solid electrolyte materials, Li7La3Zr2O 12 Garnet-type solid electrolyte materials, such as Li3PO4 and its N-substituted derivatives, glasses based on Li-BO compounds such as LiBO2 and Li3BO3 and to which Li2SO4, Li2CO3, etc. have been added, and glass ceramics can be used.
[0149] The solid electrolyte contained in the electrolyte layer 302 may include a polymer solid electrolyte. For example, a compound of a polymer compound and a lithium salt may be used as the polymer solid electrolyte contained in the electrolyte layer 302. The polymer compound may have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further increased. As the lithium salt, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. may be used. The lithium salt may be used alone or in combination of two or more kinds.
[0150] The electrolyte layer 302 may include a complex hydride solid electrolyte. Examples of the complex hydride solid electrolyte included in the electrolyte layer 302 include LiBH4-LiI and LiBH4-P2S5.
[0151] The electrolyte layer 302 may contain the above-mentioned solid electrolyte as a main component. That is, the electrolyte layer 302 may contain the solid electrolyte in a mass ratio of 50% or more (i.e., 50 mass% or more) relative to the entire electrolyte layer 302.
[0152] According to the above configuration, the output characteristics of the battery 300 can be further improved.
[0153] Furthermore, the electrolyte layer 302 may contain a solid electrolyte in a mass ratio relative to the entire electrolyte layer 302 of 70% or more (ie, 70 mass % or more).
[0154] According to the above configuration, the output characteristics of the battery 300 can be further improved.
[0155] The electrolyte layer 302 contains a solid electrolyte as a main component, and may further contain unavoidable impurities, starting materials used in synthesizing the solid electrolyte, by-products, decomposition products, and the like.
[0156] Furthermore, the electrolyte layer 302 may contain a solid electrolyte such that the mass ratio of the solid electrolyte layer 302 to the entire electrolyte layer 302 (ie, 100 mass %) is 100%, excluding unavoidable impurities.
[0157] According to the above configuration, the output characteristics of the battery 300 can be further improved.
[0158] As described above, the electrolyte layer 302 may be composed of only a solid electrolyte.
[0159] The electrolyte layer 302 may contain two or more of the materials listed as the solid electrolyte material. For example, the electrolyte layer 302 may contain a halide solid electrolyte and a sulfide solid electrolyte.
[0160] The thickness of the electrolyte layer 302 may be 1 μm or more and 300 μm or less. When the thickness of the electrolyte layer 302 is 1 μm or more, the possibility of short-circuiting between the positive electrode 301 and the negative electrode 303 is reduced. When the thickness of the electrolyte layer 302 is 300 μm or less, high-output operation is facilitated. That is, if the thickness of the electrolyte layer 302 is appropriately adjusted, sufficient safety of the battery 300 can be ensured and the battery 300 can be operated at high output.
[0161] The negative electrode 303 includes a material having the property of absorbing and releasing metal ions (for example, lithium ions). The negative electrode 303 includes a negative electrode active material 203 (for example, negative electrode active material particles).
[0162] The negative electrode active material 203 may be a metal material, a carbon material, an oxide, a nitride, a tin compound, or a silicon compound. The metal material may be a single metal. Alternatively, the metal material may be an alloy. Examples of the metal material include lithium metal or a lithium alloy. Examples of the carbon material include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, and amorphous carbon. From the viewpoint of capacity density, silicon, tin, a silicon compound, or a tin compound can be preferably used. One or a mixture of two or more selected from these materials can be used as the negative electrode active material 203.
[0163] The negative electrode 303 may include a negative electrode solid electrolyte 205. The above configuration increases the lithium ion conductivity inside the negative electrode 303, enabling high-output operation. As the negative electrode solid electrolyte 205, the materials given as examples of the solid electrolyte of the electrolyte layer 302 can be used.
[0164] The median diameter of the particles of the negative electrode active material 203 may be larger than the median diameter of the particles of the negative electrode solid electrolyte 205. This allows the negative electrode active material 203 and the negative electrode solid electrolyte 205 to be well dispersed.
[0165] The volume ratio "v2:100-v2" of the negative electrode active material 203 to the negative electrode solid electrolyte 205 contained in the negative electrode 303 may satisfy 30≦v2≦95. When 30≦v2 is satisfied, it is easy to ensure a sufficient energy density of the battery 300. When v2≦95 is satisfied, it becomes easier for the battery 300 to operate at high output.
[0166] The thickness of the negative electrode 303 may be 10 μm or more and 500 μm or less. When the thickness of the negative electrode 303 is 10 μm or more, it is easy to ensure a sufficient energy density of the battery 300. When the thickness of the negative electrode 303 is 500 μm or less, it is easier for the battery 300 to operate at high output.
[0167] At least one selected from the group consisting of the positive electrode 301, the electrolyte layer 302, and the negative electrode 303 may contain a binder for the purpose of improving adhesion between particles. The binder is used to improve the binding property of the material constituting the electrode. Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, and carboxymethyl cellulose. The binder may be a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. Two or more of these materials may be mixed and used as the binder.
[0168] At least one of the positive electrode 301 and the negative electrode 303 may contain a conductive assistant for the purpose of increasing electronic conductivity. Examples of the conductive assistant include graphites such as natural graphite or artificial graphite, carbon blacks such as acetylene black or ketjen black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymer compounds such as polyaniline, polypyrrole, or polythiophene. When a carbon conductive assistant is used, costs can be reduced.
[0169] Battery 300 in the second embodiment can be configured as batteries of various shapes, such as a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, and a laminated type.
[0170] The battery 300 in the second embodiment may be manufactured, for example, by preparing the positive electrode material, the material for forming the electrolyte layer, and the material for forming the negative electrode in the first embodiment, and fabricating a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method. EXAMPLES
[0171] Hereinafter, the present disclosure will be described in more detail using examples.
[0172] Example 1a [Preparation of solid electrolyte] In a glove box in an argon atmosphere with a dew point of -60°C or less and an oxygen value of 5 ppm or less, the raw material powders LiCl and YCl3 were weighed out so that the molar ratio was LiCl:YCl3=3:1. These raw material powders were mixed in an agate mortar to obtain a mixture. Next, the mixture was heat-treated in an inert atmosphere at 500°C for 12 hours to obtain a fired product represented by the composition formula Li3YCl6 (hereinafter referred to as LYC). The fired product was pulverized in an agate mortar to obtain LYC powder with an average particle size of 5 μm. The LYC powder was mixed with an appropriate amount of solvent and milled at 200 rpm for 20 minutes using a planetary ball mill (Fritsch, P-7 model), after which the solvent was removed and dried. As a result, LYC powder with an average particle size of 0.5 μm was obtained as a solid electrolyte. The particle size of the solid electrolyte is the median diameter, and was obtained by calculating the average value of the circle equivalent diameters of 50 particles randomly selected from the solid electrolyte particles observed at a magnification of 5000 times using a scanning electron microscope (Keyence, 3D real surface view microscope, VE-8800).
[0173] [Cathode active material] As the positive electrode active material, Li(NiCoMn)O2 (hereinafter referred to as NCM) having an average particle size of 5 μm was used.
[0174] [Preparation of coated positive electrode active material] The coating of the positive electrode active material with the solid electrolyte was carried out using a particle composite device (Nobilta, NOB-MINI, manufactured by Hosokawa Micron Corporation). 50 g of NCM and 2.5 g of LYC powder were placed in the NOB-MINI container, and the NCM and LYC were composited at a rotation speed of 6000 rpm, operating time of 15 minutes, and power value of 640 W to produce a coated positive electrode active material.
[0175] Example 1b A coated positive electrode active material was produced in the same manner as in Example 1a, except that the amount of LYC mixed was 5 g.
[0176] (Comparative Example 1a) A coated positive electrode active material was produced in the same manner as in Example 1a, except that the amount of LYC mixed was 1.25 g.
[0177] (Comparative example 1b) A coated positive electrode active material was produced in the same manner as in Example 1a, except that LYC having an average particle size of 5 μm was used instead of LYC having an average particle size of 0.5 μm.
[0178] [Measurement of coverage rate and average thickness of coating layer] The unevenness change degree, coverage rate, and average thickness of the coating layer of the coated positive electrode active material of Example 1a, Example 1b, Comparative Example 1a, and Comparative Example 1b were measured. Three arbitrarily selected particles of coated positive electrode active material were used for the measurement. The cross-sectional SEM image of the coated positive electrode active material was obtained using a scanning electron microscope (SU-70, manufactured by HITACHI). The selection of the particles of the coated positive electrode active material was performed in an average field of view where a uniform coated positive electrode active material was observed, avoiding the part where the materials such as the positive electrode active material and the solid electrolyte were aggregated. The unevenness change degree, coverage rate, and average thickness of the coating layer were calculated from the cross-sectional SEM image of the coated positive electrode active material. The results are shown in Table 1. The "coating weight ratio" is the weight ratio of the positive electrode active material to the solid electrolyte of the coating layer.
[0179] 4A and 4B are binarized images of cross-sectional SEM images of the coated positive electrode active materials of Example 1a and Comparative Example 1b, respectively.
[0180] [Table 1]
[0181] From Table 1, the coated positive electrode active materials of Examples 1a and 1b had a degree of unevenness change of 1.1 or more. The degrees of unevenness change of the coated positive electrode active materials of Examples 1a and 1b were 1.12 and 1.20, respectively. The coated positive electrode active materials of Examples 1a and 1b had a coverage ratio of 0.7 or more and 0.95 or less. The coverage ratios of the coated positive electrode active materials of Examples 1a and 1b were 0.75 and 0.92, respectively. The coating layer of the coated positive electrode active materials of Examples 1a and 1b had an average film thickness of 100 nm or more and 300 nm or less. The average film thickness of the coating layer of the coated positive electrode active materials of Examples 1a and 1b was 130 nm and 203 nm, respectively.
[0182] 4A, in the coated positive electrode active material of Example 1a, the coating layer was formed such that the black solid electrolyte filled in the concaves of the unevenness on the surface of the light gray positive electrode active material, and some of the convexities of the unevenness on the surface of the light gray positive electrode active material were exposed on the surface of the coated positive electrode active material.
[0183] The coating layer is densely formed so as to fill the concaves of the uneven surface of the positive electrode active material, thereby reducing the interface resistance when lithium ions move between the surface of the positive electrode active material and the coating layer. In addition, the convex parts of the uneven surface of the positive electrode active material are partially exposed, ensuring electronic conductivity between adjacent positive electrode active materials. This improves the charge / discharge efficiency of the battery.
[0184] 4B, in the coated positive electrode active material of Comparative Example 1b, the coating layer was formed so that the concave portions of the light gray positive electrode active material were voids. The concave portions of the uneven surface of the light gray positive electrode active material were not fully filled with the black solid electrolyte.
[0185] [Battery construction] (Example 2a, Example 2b, Comparative Examples 2a to 2c) The following steps were carried out using the coated positive electrode active materials of Example 1a, Example 1b, Comparative Example 1a, and Comparative Example 1b described above.
[0186] In a glove box in an argon atmosphere with a dew point of -60°C or less and an oxygen value of 5 ppm or less, the coated positive electrode active material of any one of Example 1a, Example 1b, Comparative Example 1a, and Comparative Example 1b and the positive electrode solid electrolyte Li2S-P2S5 were weighed. The volume ratio of the positive electrode active material to the total of the solid electrolyte forming the coating layer and the positive electrode solid electrolyte was 60:40. These were mixed in an agate mortar to produce the positive electrode materials of Example 2a, Example 2b, Comparative Example 2a, and Comparative Example 2b.
[0187] An electrolyte layer was obtained by putting 80 mg of Li2S-P2S5 into an insulating outer cylinder and pressurizing and molding the same at a pressure of 80 MPa. Next, 14 mg of the positive electrode material of any one of Example 1a, Example 1b, Comparative Example 1a, and Comparative Example 1b was put into the insulating outer cylinder in an amount equivalent to a positive electrode active material, and pressurized and molded at a pressure of 720 MPa to obtain a positive electrode layer. Next, metal In (thickness 200 μm), metal Li (thickness 300 μm), and metal In (thickness 200 μm) were laminated in this order on the electrolyte layer on the counter electrode side. This was pressurized and molded at a pressure of 80 MPa to obtain a negative electrode layer. Next, stainless steel current collectors were placed above and below the laminate including the positive electrode layer, electrolyte layer, and negative electrode layer, and a current collecting lead was attached to the current collector. Finally, an insulating ferrule was used to isolate the inside of the insulating outer cylinder from the outside atmosphere, and the insulating outer cylinder was sealed to produce a battery. The inner diameter of the insulating outer cylinder used in this example was 9.5 mm, and the projected area of the electrode was 0.71 cm 2 It was.
[0188] (Comparative Example 2c) A battery was fabricated in the same manner as in Example 2a, except that a positive electrode active material without a coating layer was used as the positive electrode material.
[0189] Using the batteries of Example 2a, Example 2b, Comparative Example 2a, Comparative Example 2b, and Comparative Example 2c described above, battery evaluation was carried out under the following conditions.
[0190] The batteries of the example and comparative example were placed in a thermostatic chamber at 85°C.
[0191] The battery was charged at a constant current of 140μA, which is 0.05C rate (20 hour rate) for the theoretical capacity of the battery, and the voltage was 3.68V (Li / Li + The charging was terminated at a voltage of 3.68 V, which corresponds to a current of 28 μA or less, which corresponds to a 0.01 C rate. After charging, the interface resistance between the coated positive electrode active material and the positive electrode solid electrolyte was determined by impedance measurement using the AC impedance method. The impedance measurement conditions were a voltage amplitude of 5 mV, a measurement frequency of 1 MHz to 0.1 Hz, and 85°C. The results are shown in Table 2. Next, the battery was left to stand for 3 days in an open circuit state. Next, the battery was discharged at a current of 140 μA, which corresponds to a 0.05 C rate, until the voltage reached 1.88 V (Li / Li + Discharge was terminated at a voltage of 2.5 V (based on the reference voltage).
[0192] As a result, the discharge capacity and capacity efficiency of each battery of the above-mentioned Examples and Comparative Examples were obtained. The results are shown in Table 2 below. Capacity efficiency is the ratio of discharge capacity to charge capacity. Capacity efficiency has the same meaning as charge / discharge efficiency.
[0193] From Table 2, the batteries of Examples 2a and 2b exhibited higher discharge capacity and capacity efficiency than the batteries of Comparative Examples 2a to 2c, and the batteries of Examples 2a and 2b exhibited lower interface resistance than the batteries of Comparative Examples 2a to 2c.
[0194] [Table 2]
[0195] Example 3 A battery was fabricated in the same manner as in Example 2a, except that Li3YCl6 was used as the positive electrode solid electrolyte of the positive electrode material.
[0196] (Comparative example 3a) A battery was fabricated in the same manner as in Comparative Example 2b, except that Li3YCl6 was used as the positive electrode solid electrolyte of the positive electrode material.
[0197] (Comparative example 3b) A battery was fabricated in the same manner as in Comparative Example 2c, except that Li3YCl6 was used as the positive electrode solid electrolyte of the positive electrode material.
[0198] Using the batteries of Example 3, Comparative Example 3a, and Comparative Example 3b described above, battery evaluation was carried out under the same conditions as in Example 2a, and the results are shown in Table 3 below.
[0199] From Table 3, even when a halide solid electrolyte was used as the positive electrode solid electrolyte, the battery of Example 3 exhibited higher discharge capacity and capacity efficiency than the batteries of Comparative Examples 3a and 3b. Also, the battery of Example 3 exhibited lower interface resistance than the batteries of Comparative Examples 3a and 3b.
[0200] [Table 3]
[0201] Example 4 A battery was fabricated in the same manner as in Example 2a, except that an NCM having a lithium niobate coating with an average thickness of 6 nm was used, Li3YBr2Cl4 was used as the positive electrode solid electrolyte, and 2 wt% of a conductive additive (VGCF-H, Showa Denko K.K.) was added to the positive electrode material relative to the positive electrode active material.
[0202] Comparative Example 4 A battery was fabricated in the same manner as in Comparative Example 2b, except that an NCM having a lithium niobate coating with an average thickness of 6 nm was used, Li3YBr2Cl4 was used as the positive electrode solid electrolyte, and 2% by weight of a conductive additive (VGCF-H) was added to the positive electrode material relative to the positive electrode active material.
[0203] Battery evaluation was carried out under the same conditions as in Example 2a using the batteries of Example 4 and Comparative Example 4. The results are shown in Table 4 below.
[0204] From Table 4, even when a halide solid electrolyte having a composition different from that of the solid electrolyte of the coating layer was used for the positive electrode solid electrolyte, the battery of Example 4 exhibited higher discharge capacity and capacity efficiency than the battery of Comparative Example 4. The battery of Example 4 exhibited lower interface resistance than the battery of Comparative Example 4.
[0205] [Table 4] [Industrial Applicability]
[0206] The technology of the present disclosure is useful, for example, in all-solid-state lithium-ion secondary batteries. [Explanation of symbols]
[0207] 100 Coated positive electrode active material 101 Cathode active material 102 Solid electrolyte (coating layer) 202 Positive electrode solid electrolyte 203 Negative electrode active material 205 Negative solid electrolyte 300 batteries 301 Positive electrode 302 Electrolyte layer 303 Negative electrode 1000 Positive Electrode Materials
Claims
1. A coated positive electrode active material comprising a particulate positive electrode active material and a solid electrolyte that coats a surface of the positive electrode active material, The solid electrolyte forms a coating layer, the coating layer is formed such that recesses on the surface of the positive electrode active material are filled with the solid electrolyte, a protrusion on the surface of the positive electrode active material is exposed on a surface of the coated positive electrode active material, The unevenness ζ of the particle group is defined by the following formula (1): [0010] In the formula (1), n is an integer of 3 or more and represents the number of particles measured, Lpi represents the total perimeter of the outline of the cross-sectional image of each particle, Lei represents the total perimeter of an equivalent smooth ellipse having a major / minor ratio and an area equal to the major / minor ratio and the area of the cross-sectional image of each particle, and the major / minor ratio represents the ratio of the minor axis of the cross-sectional image to the major axis of the cross-sectional image, The unevenness of the particle group of the positive electrode active material is ζ 1 and the unevenness of the particle group of the coated positive electrode active material is defined as ζ 2 When the above formula is defined, the unevenness change degree R defined by the following formula (2) is 1.1 or more, R=ζ 2 / g 1 ・・・(2) The solid electrolyte has a composition represented by the following formula (3): Li α M β Cl γ ・・・(3) In the formula (3), α, β, and γ are values greater than 0, and M includes at least one selected from the group consisting of metal elements and semimetal elements other than Li. Coated positive electrode active material.
2. a ratio of the mass of the solid electrolyte to the mass of the positive electrode active material is in the range of 3 / 100 or more and 1 / 10 or less; The coated positive electrode active material according to claim 1 .
3. a ratio of the mass of the solid electrolyte to the mass of the positive electrode active material is in the range of 1 / 20 or more and 7 / 100 or less; The coated positive electrode active material according to claim 1 .
4. In the cross-sectional image of the coated positive electrode active material, when the total perimeter length of the outline of the positive electrode active material is defined as L and the total length of the contact portion between the positive electrode active material and the coating layer is defined as C, A coverage ratio represented by a ratio C / L of the total length C to the total circumferential length L is in the range of 0.3 to 0.
95. The coated positive electrode active material according to claim 1 .
5. The average thickness of the coating layer is in the range of 1 nm or more and 300 nm or less. The coated positive electrode active material according to claim 1 .
6. The average thickness of the coating layer is in the range of 2 nm to 200 nm. The coated positive electrode active material according to claim 1 .
7. The M includes yttrium. The coated positive electrode active material according to claim 1 .
8. The α, β, and γ satisfy 2.5≦α≦3, 1≦β≦1.1, and γ=6, respectively. The coated positive electrode active material according to claim 1 .
9. The positive electrode active material includes lithium nickel-cobalt-manganese oxide. The coated positive electrode active material according to claim 1 .
10. The positive electrode active material has a surface layer containing lithium metal oxide. The coated positive electrode active material according to claim 1 .
11. The lithium metal oxide includes lithium niobate. The coated positive electrode active material according to claim 10.
12. The coated positive electrode active material according to any one of claims 1 to 11, A positive electrode solid electrolyte; A positive electrode material comprising:
13. The positive electrode solid electrolyte includes a halide solid electrolyte. The positive electrode material of claim 12.
14. The positive electrode solid electrolyte includes a sulfide solid electrolyte. The positive electrode material according to claim 12 or 13.
15. A positive electrode comprising the positive electrode material according to any one of claims 12 to 14; A negative electrode; an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with a battery.
16. the electrolyte layer includes at least one selected from the group consisting of a solid electrolyte having the same composition as the solid electrolyte included in the coating layer and a solid electrolyte having the same composition as the positive electrode solid electrolyte, 16. The battery of claim 15.
17. The electrolyte layer includes a halide solid electrolyte having a composition different from the composition of the solid electrolyte contained in the coating layer and / or the composition of the positive electrode solid electrolyte.
16. The battery of claim 15.
18. The electrolyte layer includes a sulfide solid electrolyte.
18. The battery of any one of claims 15 to 17.
19. A method for producing a coated positive electrode active material according to any one of claims 1 to 11, treating the positive electrode active material and the solid electrolyte by a dry particle composite method; The treatment by the dry particle compositing method includes applying at least one mechanical energy selected from the group consisting of impact, compression, and shear to the positive electrode active material and the solid electrolyte. A method for producing a coated positive electrode active material.
20. a ratio Da / Dc of an average particle diameter Da of the positive electrode active material to an average particle diameter Dc of the solid electrolyte is 2 or more; The method for producing the coated positive electrode active material according to claim 19.
21. a ratio Da / Dc of an average particle diameter Da of the positive electrode active material to an average particle diameter Dc of the solid electrolyte is 5 or more; The method for producing the coated positive electrode active material according to claim 19.
Citation Information
Patent Citations
Titanium niobate negative electrode material and preparation method and application thereof
CN110931730A
Entirely solid lithium secondary battery
JP2001052733A
Composite particle for electrode and electrochemical device
JP2009087682A
Structured silicon particles
JP2015513180A
Composite positive electrode active material for all-solid-state secondary battery, method for manufacturing same, positive electrode, and all-solid-state secondary battery
WO2018038037A1